Individualni pristop v zdravsteni negi dementnega varovanca v okviru življenjskih aktivnosti - Majerle, Stanka (Obzornik zdravstvene nege, 2000)
The article brings the definition of dementia as described in the 10th Revision of the International Classification of Diseases. It lists the most frequent symptoms of dementia which are divided into different stages, indicating problems nurses encounter when working with a patient with dementia. It describes all the physical activities of a person that are affected: eating and drinking, personal hygiene, dressing and undressing, recreation and elimination, sleeping and resting, ability to communicate, sense of direction, movement, emotions and behaviour.
Keywords: Activities of daily living; bolniki; demenca; Dementia; Nursing; zdravstvena nega